Adrenocortical Zonation, Renewal, and Remodeling - Pihlajoki, Marjut; Dörner, Julia; Cochran, Rebecca S.; Heikinheimo, Markku; Wilson, David B. (Frontiers in Endocrinology, 2015)
The adrenal cortex is divided into concentric zones. In humans the major cortical zones are the zona glomerulosa, zona fasciculata, and zona reticularis. The adrenal cortex is a dynamic organ in which senescent cells are replaced by newly differentiated ones. This constant renewal facilitates organ remodeling in response to physiological demand for steroids. Cortical zones can reversibly expand, contract, or alter their biochemical profiles to accommodate needs. Pools of stem/progenitor cells in the adrenal capsule, subcapsular region, and juxtamedullary region can differentiate to repopulate or expand zones. Some of these pools appear to be activated only during specific developmental windows or in response to extreme physiological demand. Senescent cells can also be replenished through direct lineage conversion; for example, cells in the zona glomerulosa can transform into cells of the zona fasciculata. Adrenocortical cell differentiation, renewal, and function are regulated by a variety of endocrine/paracrine factors including adrenocorticotropin, angiotensin II, insulin-related growth hormones, luteinizing hormone, activin, and inhibin. Additionally, zonation and regeneration of the adrenal cortex are controlled by developmental signaling pathways, such as the sonic hedgehog, delta-like homolog 1, fibroblast growth factor, and WNT/β-catenin pathways. The mechanisms involved in adrenocortical remodeling are complex and redundant so as to fulfill the offsetting goals of organ homeostasis and stress adaptation.